Development and Characterization of a Combination Tablet Dosage Form Containing Sofosbuvir and Ribavirin Using Design of Experiments (DoE) Approach - Islam, Md Anisul; Alam, Md Mahbubul; Sikdar, KM Yasif Kayes; Hossain, ASM Monjur Al; Rouf, Abu Shara Shamsur (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Worldwide more than 180 million people get infected by chronic Hepatitis C Virus (HCV) and around 700,000 people pass away every year due to HCV related problems. Sofosbuvir and Ribavirin are prescribed as combined medication for the management of HCV infection globally. Therefore, optimization of a pharmaceutical dosage form containing Sofosbuvir and Ribavirin can open a new hope in the treatment of HCV infection. This study was conducted by using the Design of Experiments (DoE) approach. It is a systematic process aiming to determine the correlation between formulation factors affecting the approach and the output of the approach. During the development of formulations, two factors were considered, which are Croscarmellose Sodium (CCS) and Povidone K30 (PK30) at different concentrations ranging from 0.19% to 2.31% of the total tablet weight in 9 different formulations. Their effect on disintegration time (DT) was evaluated through statistical method and it was found between 3±0.003 and 6.5±0.015 minutes. The use of these two different disintegrants exhibited a significant effect on DT. The contour plot showed predicted ranges of concentrations of CCS and PK30 for desired DT. Fourier Transform Infrared Spectroscopy (FTIR) data, Thermogravimetric Analysis (TGA) and X-ray Diffractometry (XRD) spectrums confirmed that there was no interaction between Sofosbuvir and Ribavirin or with any other excipients used in this experiment. Dhaka Univ. J. Pharm. Sci. 20(1): 121-133, 2021 (June)